Mobility and Orientation Guidance for Individuals with Visual Impairments using AI - Ishraq Uddin, Chowdhury; Muhammad Imtiaz Uddin, Chowdhury; Md Safaet, Hossain (INTI International University, 2025)
In this study, we developed an intelligent device and a smart application to improve the daily activities of the visually impaired individuals. Low-vision or blind people often face a number of barriers in the course of completing everyday tasks. Learning about roadways, purchasing commodities, reading written books, and digesting new information is significantly harder. To this end, a gadget was created to counter these obstacles. People with deficient eyesight or complete blindness can now enjoy the effect of reading books and articles in real-time using OCR and AI-powered technology. They can also recognize things, goods, and people, including visual information like facial expressions. In addition, haptic feedback through bone-conducting headphones gives multilingual notifications of either vehicle movement or road condition.